Kepuasan pernikahan pada pasangan commuter marriage: Bagaimana peranan problem solving? - mochammad osvaldo millian ramadhan; Tatik Meiyuntariningsih; Akta Ririn Aristawati (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between problem solving and marital satisfaction in commuter marriages. The research design uses a correlational quantitative research method. This research was conducted on 57 participants with long-distance relationship status or what can be called a commuter marriage which was taken using the non-probability method with snowball sampling. Based on the calculation of the analysis of hypothesis testing with Spearman's Rho correlation, the results of a correlation value (r) of 0.445 with a significance value of 0.001 (sig. <0.05), which means there is a positive relationship between the problem solving and marital satisfaction in commuter marriages. This means that the higher the problem-solving of married couples, the higher the marital satisfaction of commuter marriage couples. Keywords: marital satisfaction, Problem-Solving, Commuter Marriage